Covered stenting and transcatheter embolization of splenic artery aneurysms in diabetic patients: A review of endovascular treatment of visceral artery aneurysms in the current era. (September 2018) - Venturini, Massimo; Marra, Paolo; Colarieti, Anna; Agostini, Giulia; Lanza, Carolina; Augello, Luigi; Gusmini, Simone; Salvioni, Marco; Melissano, Germano; Fiorina, Paolo; Chiesa, Roberto; De Cobelli, Francesco; et al.
Abstract: Diabetes mellitus is associated with both microvascular and macrovascular complications, which can result in visceral aneurysms as for example splenic artery aneurysms: in their management, an endovascular treatment, less invasive than surgery, is generally preferred. Endovascular treatment of splenic artery aneurysms can be based either on covered stenting (CS) or transcatheter embolization (TE). CS generally allows aneurysm exclusion with vessel preservation, while TE usually determines target artery occlusion with potential risk of distal ischemia. We performed a review of the existing literature on endovascular treatment of visceral artery aneurysms (VAAs) and psudoaneurysms (VAPAs) in the current era.